Effect of feeding hens trout by-product meal or tuna fish oil on production parameters and yolk fatty acid profile - Díaz, Gonzalo J; Cortés, Amparo; Cepeda, Sandra M (Revista Colombiana de Ciencias Pecuarias, 2012)
Summary Objective: a study was conducted to evaluate two sources of omega-3 (n-3) fatty acid enrichment, namely a trout by-product meal (TBPM) and tuna fish oil (TFO), as potential sources for egg yolk n-3 enrichment. Methods: seventy-27 week old commercial layers were assigned to each of seven dietary treatments, as follows. Group 1: control; group 2: 5% TBPM; group 3: 10% TBPM; group 4: 15% TBPM; group 5: 20% TBPM; group 6: 2% TFO; and group 7: 3% TFO. The experimental diets were fed for 28 days. Results: no effect on production parameters was caused by the experimental diets. All diets containing TBPM or TFO significantly (p < 0.05) increased n-3 egg yolk fatty acid content. Dietary levels of 5-20% TBPM increased egg yolk n-3 content between 1.97 and 3.54 times compared with control eggs. TFO levels of 2% and 3% increased the n-3 egg yolk content 3.37 and 4.13 times, respectively, compared with control eggs. The n-6/n-3 ratio in egg yolk lipids was significantly (p < 0.05) decreased by the experimental diets. The n-6/n-3 ratio in control eggs was 16.79 compared with ratios ranging from 4.34 to 8.11 in enriched eggs. Conclusions: the results showed that both TBPM and TFO are good sources of n-3 fatty acid enrichment in eggs. Further studies are required in order to determine the effects of TBPM and TFO inclusion on the organoleptic quality of eggs. Key words: hens, n-3 fatty acids, omega-3 eggs, trout by-product meal , tuna fish oil. Resumen Objetivo: se realizó un estudio para evaluar dos potenciales fuentes de enriquecimiento de ácidos grasos omega-3 (n-3) en yema de huevo: ensilaje de vísceras de trucha (TBPM) y aceite de atún (TFO). Métodos: un total de 70 gallinas de postura de 27 semanas se asignaron a siete tratamientos dietarios, así: grupo 1: control; grupo 2: 5% TBPM; grupo 3: 10% TBPM; grupo 4: 15% TBPM; grupo 5: 20% TBPM; grupo 6: 2% TFO y grupo 7: 3% TFO. Las dietas experimentales se suministraron durante 28 días. Resultados: no se encontraron efectos sobre los parámetros productivos a causa de las dietas experimentales, pero todas las dietas suplementadas con TBPM o TFO causaron un aumento significativo (p < 0.05) en el contenido de n-3 de la yema. La suplementación de 5-20% de TBPM causó un incremento de n-3 de 1.97 a 3.54 veces, comparado con el contenido de n-3 de los huevos control. La suplementación de 2% y 3% de TFO incrementó en contenido de n-3 en 3.37 y 4.13 veces, respectivamente. La relación n-6/n-3 en los lípidos de la yema aumentó significativamente en las dietas experimentales siendo esta relación de 16.79 en los huevos control y de 4.34-8.11 en los huevos de gallinas suplementadas con las fuentes de n-3. Conclusiones: los resultados del presente estudio demuestran que tanto el TBPM como el TFO constituyen fuentes apropiadas de enriquecimiento de huevos con ácidos grasos n-3. Se requieren más estudios para determinar los efectos de estas materias primas en la calidad organoléptica del huevo. Palabras clave: aceite de atún, ácidos grasos n-3, ensilaje de vísceras de trucha, gallinas de postura. Resumo Objetivo: foi realizado um estudo para avaliar duas fontes potenciais de enriquecimento de ômega-3 (n-3) na gema de ovo: silagem de vísceras de truta (TBPM) e óleo de atum (TFO). Métodos: um total de 70 galinhas poedeiras de 27 semanas, foram atribuídas a sete tratamentos dietéticos: grupo 1: controle, grupo 2: 5%TBPM, grupo 3: 10% TBPM, grupo 4: 15% TBPM, grupo 5: 20% TBPM, grupo 6: 2% TFO e grupo 7: TFO 3%. As dietas experimentais foram subministradas durante 28 dias. Resultados: não foram encontradas diferencias nos parâmetros de produção por causa das dietas experimentais, mas todas as dietas suplementadas com TFO ou TBPM causaram um aumento significativo (p < 0.05) no conteúdo de n-3 da gema. A suplementação de 5-20% de TBPM causou um aumento de n-3 de 1.97 a 3.54 vezes, em comparação com o conteúdo de n-3 do controle. A suplementação de 2% e 3% de TFO aumentou o conteúdo de n-3 em 3.37 e 4.13 vezes, respectivamente. A relação n-6/n-3 nos lipídios da gema aumentou significativamente nas dietas experimentais, sendo esta relação de 16.79 nos ovos do controle e de 4.43 a 8.11 em ovos de galinha suplementados com fontes de n-3. Conclusões: os resultados deste estudo demonstram que o TFO e o TBPM são fontes apropriadas de enriquecimento de ovos com n-3 ácidos graxos. Mais estudos são necessários para determinar os efeitos dessas matérias primas na qualidade organoléptica do ovo. Palavras chave: ácidos graxos, avicultura, óleo de atum.